1991
DOI: 10.1002/jso.2930460108
|View full text |Cite
|
Sign up to set email alerts
|

Two prostate carcinoma cell lines demonstrate abnormalities in tumor suppressor genes

Abstract: Two prostate carcinoma cell lines, DU-145 and PC-3, were examined for abnormalities in the retinoblastoma (Rb) and the p53 putative tumor suppressor genes. We found an abnormal Rb gene product in DU-145 using Western blot analysis. Polymerase chain reaction amplification followed by direct DNA sequencing demonstrated a base substitution mutation that generates a stop codon in exon 21. On Northern, Southern, and Western blot analysis, the p53 gene and its product appear to be normal in DU-145. PC-3, however, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 40 publications
5
54
1
Order By: Relevance
“…PC3 cells do not express endogenous p53 protein due to a gross deletion of one allele and a single base-pair deletion in the remaining allele (Isaacs et al, 1991;Rubin et al, 1991;Carroll et al, 1993). As expected, p53 protein expression was not detected at any time point after control virus infection (data not shown).…”
Section: Adenovirus-p53 Infection Of Vector Control and Bcl-2-overexpsupporting
confidence: 72%
“…PC3 cells do not express endogenous p53 protein due to a gross deletion of one allele and a single base-pair deletion in the remaining allele (Isaacs et al, 1991;Rubin et al, 1991;Carroll et al, 1993). As expected, p53 protein expression was not detected at any time point after control virus infection (data not shown).…”
Section: Adenovirus-p53 Infection Of Vector Control and Bcl-2-overexpsupporting
confidence: 72%
“…We observed that the human prostate cancer cell lines, LNCaP, DU-145 and PC-3, which differ in their status of p53, 18 expressed different levels of EMMPRIN (Fig. 1A).…”
Section: Effects Of P53 Status On Emmprin Protein Expressionmentioning
confidence: 94%
“…There was also an increase in p53 protein levels at T ¼ 6 and 8 h in both cell types. It is noted that MCF-7 has wild-type p53 and wild-type Rb genes, while DU-145 contains a single mutant p53 allele encoding a double point mutant p53 protein and a mutant Rb allele with an internal in-frame deletion of exon 21 (Rubin et al, 1991;Wosikowski et al, 1995). Since BRCA1 protein was similarly lost during heating of both cell types, it is unlikely that the p53 or Rb status of these cell lines was a critical factor in the regulation of BRCA1 protein levels under heat shock conditions.…”
Section: Disappearance Of Brca1 Protein During the Heat Shock Responsementioning
confidence: 99%